Narrative Study of Teacher Students’ Experiences on an Experimental Chemistry Field Course in Finland - Nuora, Piia; Välisaari, Jouni (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
The aim of this study was to investigate chemistry teacher students’ experiences of an experimental chemistry field course. A narrative approach was used because the aim was to obtain authentic reports. The study participants (N = 8) had all taken part in an experimental chemistry field course between 2013 and 2015. The teacher students reported that once they had participated in the field course, they were ready to teach science outside the classroom with students in future. Without the field course, they would be less likely to do so. The results indicate that chemistry teacher students feel they need more training in different learning environments.